Impacto psicoemocional de uma investigação criminal sobre violência sexual na criança promovida por seus familiares - Bianco, Mariana Melo (2021)
Sexual violence, when it occurs particularly in a domestic context with children or adolescents, is characterized by the silence from occasional witnesses and, most often, from the victim‟s family. This situation is one of the main factors contributing to the underreporting of these cases in our country. When legal proceedings are instituted, other damages may arise, in addition to those already experienced with the sexual abuse. This study aimed to investigate whether recurrent questions made to a victim of sexual violence during a court procedure could reinforce the psychoemotional impacts already caused by the violence and whether such questions could lead to a revictimization of the child. Its specific objective: to reflect on whether the action of the Law or the Judiciary Power can contribute, even if occasionally, to increase the psychological and emotional discomfort of sexually abused children. A qualitative research was carried out, with a Case Study design, supported by a set of documents selected from a Police Inquiry referring to a girl allegedly sexually abused at the age of three by her father and paternal grandparents. The Document Analysis, expanded by the Timeline and Genogram instruments, verified that the investigative procedure could have been conducted differently and quicker, aiming at a more adequate response from the child's health perspective. The numerous and successive interviews carried out with the girl in different sectors and with various professionals and the delay in completing the investigation, which lasted from the child's 3.0 to 7.0 years of age, undoubtedly influenced the changes in her narrative due to her level of physical and psychological development. The professionals who evaluated her soon after the alleged sexual abuse concluded that the violence was possible, diagnosed symptoms of PTSD (Post Traumatic Stress Disorder), and referred her for psychotherapeutic treatment. However, evaluations carried out later concluded for the false accusation of the child's father and paternal grandparents. A rapprochement was suggested between the girl and the paternal family, causing the reappearance of PTSD symptoms and indicating the child's revictimization during the procedure. Reflections, criticisms, and suggestions were made at the end of this work so that other cases have a different outcome from the one analyzed